Development of Integrated Android Physical Flipbook with Pancasila Values on Newton’s Law Material - Arifin, I; Ariswan, A (Department of Physics, Faculty of Mathematics and Natural Sciences, 2022)
Pancasila is the basis of the state and ideology of the Indonesian nation. However, the practice of Pancasila values as the character of the Indonesian nation in everyday life has decreased. Therefore, it is important to integrate Pancasila into learning a strengthen student character education. The study aims to (1) develop an integrated android physics flipbook product with Pancasila values in Newton's Law material and (2) determine the feasibility of the product being developed. This research is development research. The development model used is the 4D model (define, design, develop, and disseminate). The development is carried out by involving a material expert, a media expert, two teachers, and a colleague. The product trial stage was carried out by involving 36 students of class XI MIA 1 SMA Negeri 1 Prambanan Klaten. Data analysis used quantitative analysis with descriptive statistics. This study shows that the Flipbook media developed has the advantage of Newton's Law material which is integrated with Pancasila values, has a media aspect assessment score of 3.93 with a very good category, material aspect of 3.89 with a very good category, and student responses during trials. of 3.34 with good category. Furthermore, teachers or other researchers can develop learning media that are integrated with Pancasila values for other physics materials.